A diagnostic dilemma of an 18-week cervical ectopic pregnancy: A case report - Sarah Coulter-Nile; Kapilesh Balachandar; Harvey Ward (Elsevier, 2022)
Introduction: Cervical ectopic pregnancy (CEP) is characterised by the implantation of trophoblastic tissue within the cervical canal and is associated with a significant risk of maternal morbidity and mortality. This case report addresses a second-trimester CEP with unusual sonographic features suspicious of placenta accreta spectrum (PAS), which was successfully managed with an abdominal hysterectomy. Case Presentation: A 27-year-old woman, G6P2, presented to the labour ward of a rural hospital at 18 weeks of gestation with premature rupture of membranes. The index pregnancy was complicated by an absence of any antenatal care, as well as a history of cigarette smoking and cannabis use. An ultrasound scan demonstrated a live pregnancy with the foetal head within the cervical canal. A termination of pregnancy was arranged with misoprostol 200 mg orally followed by an oxytocin induction. However, a repeat ultrasound scan, after 12 h of oxytocin infusion, which failed to terminate the pregnancy, demonstrated a still live foetus as well as increased vascularity, concerning for PAS. The patient underwent an emergency abdominal hysterectomy, with an intraoperative diagnosis of a CEP. The postoperative course was unremarkable, and the patient was discharged home on day 3 post-operatively. Discussion: Appropriate antenatal care and early booking-in would have identified a CEP early in gestation and allowed for minimally invasive management and potential conservation of fertility. When this is not possible in such cases, meticulous pre-operative planning by a gynaecologist with experience in advanced pelvic surgery can minimise the associated morbidity and mortality.